Differences in maturation of tick-borne encephalitis virus in mammalian and tick cell line - Senigl, Filip; Grubhoffer, Libor; Kopecky, Jan (Intervirology, 2006)
OBJECTIVE: The maturation process of tick-borne encephalitis virus (TBEV) in the tick RA-257 and porcine PS cells was studied by transmission electron microscopy and the E and NS1 proteins were localized in the infected cells. METHODS: The porcine PS and tick RA-257 cell lines were infected with TBEV and examined at different time points post infection under an electron microscope. The E and NS1 proteins were localized with monoclonal antibodies on ultrathin cryosections. RESULTS: The first virus particles and virus-induced vesicles appeared inside hypertrophied and dilated rough endoplasmic reticulum (RER) cisternae in PS cells 15 h p.i. In the course of progressing maturation, the virus particles came up inside the Golgi apparatus and then probably left the cell by the exocytic pathway. Free nucleocapsids did not appear. The observed pattern corresponded to a trans-type maturation. The maximum of the infected PS cell survival was about 50 h p.i. Immunolocalization of some viral proteins (the envelope protein E and the nonstructural protein NS1) revealed the proteins in the cytosol and on the membrane of hypertrophied RER cisternae. On the other hand, the maturation process exhibited different features in the case of the tick RA-257 cells. The nucleocapsids appeared in the cytosol 24 h p.i. and enveloped viral particles were observed in the lumen of vacuoles. Infection of RA-257 cells caused only minor ultrastructural changes and resulted in persistent infection. Immunolocalization of viral proteins in the tick cell line also differed. Proteins E and NS1 were localized in the cytosol and on the vacuolar and plasma membranes. CONCLUSION: The TBEV maturation pathway in the mammalian host cell line differs from the pathway that the virus undergoes in the tick vector cell line.
Keywords: členovci - vektory; Encephalitis Viruses, Tick-Borne; Endoplasmic Reticulum, Rough; Ticks; Arthropod Vectors; Viral Proteins; viry klíšťové encefalitidy; drsné endoplazmatické retikulum; zvířata; Immunohistochemistry; imunohistochemie; časové faktory; Swine; buněčné linie; virové proteiny; Cell Line; vakuoly; klíšťata; Animals; Vacuoles; Time Factors; prasata